For debate: the Operational Patient Care Pathway. Issue 1 (29th January 2014) - Bricknell, Martin
Abstract : This paper introduces the Operational Patient Care Pathway which is a unified approach for clinical care to all operational patients arising from the Defence population at risk (PAR) exposed to the 'all-hazards environment' while deployed on military operations. It comprises three organisational models: the Healthcare Cycle, the Chain of Care and the Operational Patient Care Pathway. It is supported by a number key definitions including: the 'All-Hazards Environment', the Defence PAR, and the seven Capabilities of Operational Healthcare. Key new clinical concepts include: Tactical Field Care, Care under Fire, Enhanced Field Care, Prolonged Field Care, Progressive Resuscitation and Enhanced Diagnostics. The Operational Patient Care Pathway has been introduced to embed the medical lessons from the last decade of military operations into concepts and doctrine for the Defence Medical Services of the future. Readers of this journal are encouraged to debate the Operational Patient Care Pathway paper in order to enable a final version to be published in the next revision of Joint Medical Doctrine.